1321. Increased Prevalence of Group A Streptococcus (GAS) High Level Macrolide Resistance During the COVID-19 Pandemic. (15th December 2022) - Patel, Ami B; Guzman-Cottrill, Judith A; Fleming-Dutra, Katherine E; Chochua, Sopio; Beall, Bernard; Jaggi, Preeti; Rippe, Jason; Inguglia, Christine L; Katsogridakis, Yiannis L; Ozer, Egon A; Shulman, Stanford; Tanz, Robert R
Abstract: Background: COVID-19 affected the epidemiology of many respiratory pathogens including GAS. Assessing genetic heterogeneity ( emm type, antimicrobial resistance, virulence factors) can inform treatment recommendations and targets for potential GAS vaccines. We assessed GAS clinical antibiotic susceptibility and performed whole genome sequencing (WGS) among pediatric pharyngeal isolates from 2020–2022. Methods: From 1/2020–3/2022 we collected throat swabs in pediatric clinics and EDs from children aged 3-18 years in Chicago, IL; Atlanta, GA; Portland, OR; and Phoenix, AZ: 1) with acute GAS pharyngitis and 2) among a convenience sample of asymptomatic children to assess for GAS colonization. Swabs were plated on blood agar. E-tests were used to assess clinical susceptibility to erythromycin (ERY) and ciprofloxacin (CIP). emm type and antimicrobial resistance genes (ERY, Clindamycin (CLI), and fluoroquinolones) were assessed by WGS. Results: 1144 pharyngeal swabs were collected: 359/684 (52%) from children with GAS pharyngitis by rapid test and 20/460 (4.3%) from asymptomatic children yielded GAS on culture. Phenotypic resistance : 55/364 (15%) tested isolates were ERY resistant and 5/364 (1.4%) CIP resistant. The proportion of isolates with ERY resistance increased significantly from 2020 (6%) to 2021–2022 (25%) (χ 2 = 23.70, p< .00001) (Figure 1). MICs were high among ERY resistant GAS (Table 1). Genotypic resistance: Of 304 sequenced GAS isolates 40/304 (13%) were ERY resistant, 35/304 (11.5%) were both ERY resistant and CLI (inducible or constitutive) resistant, and 4/304 (1.3%) fluoroquinolone resistant. e rm B (62%) was the most common gene for ERY resistance and constitutive CLI resistance, followed by erm TR (23%) and erm T (11%) both conferring inducible CLI resistance. Among the 20 isolates from asymptomatic children no ERY, CLI, or CIP resistance occurred, and no resistance genes were identified. emm types 11, 9, 77, 58 and 94 were associated with ERY and CLI resistance. Conclusion: ERY resistance increased from 2020–2022. The high rate of CLI resistance among ERY resistant GAS was associated with erm genes. These results are important to inform treatment recommendations for GAS pharyngitis and targets for vaccine development that can reduce antimicrobial-resistant GAS disease. Disclosures: All Authors : No reported disclosures.